Mathematical model and dynamic analysis of pendulum system excitation via an electro-dynamical shaker - Marques, Carlos Eduardo [UNESP]; Balthazar, Jose Manoel [UNESP]; Ribeiro, Mauricio Aparecido; Lenz, Wagner Barth; Tusset, Angelo Marcelo (My University, 2020)
In this paper, we present a mathematical model and numerical investigations of a pendulum system excited by an EDS (Electro-Dynamical Shaker). The dynamic analysis is considered by history of the time, phase plane, Poincaré map, bifurcation diagram, FFT and Lyapunov Exponent. Numerical simulations demonstrate that the model has quasi-periodic or periodic behavior for certain range of parameters.
Keywords: Chaotic oscillations; Energy harvesting; Mechanical vibrations; Nonlinear systems